A RETROSPECTIVE COHORT STUDY ON REDUCED PRE-INCISION ANTIBIOTIC INFUSION TIME: EFFECTS ON SURGICAL SITE INFECTION RATES. - Tomar, Surabhi; Dhakarey, Sujay Singh (Student’s Journal of Health Research Africa, 2024)
Background: One important factor contributing to postoperative morbidity and mortality is surgical site infections (SSIs). It has been demonstrated that promptly administering preoperative antibiotics lowers the risk of SSIs. This study aimed to look at how SSI rates among patients taking cefazolin or vancomycin for pre-operative SSI prophylaxis were affected by a shorter pre-incision antibiotic infusion period. Methods: Data on pre-operative antibiotic administration, surgical services, operation schedule, and post-operative infection were gathered from 98 patients who were enrolled in a retrospective cohort analysis. Based on when the antibiotics were infused during the surgery, the patients were categorized into groups. To evaluate the relationship between pre-incision antibiotic infusion time and SSI rates, statistical analysis was done. Results: Of the patients, 60% were male, with a mean age of 52 years. Most of the patients (70%) received cefazolin, while 30% received vancomycin. Analysis revealed that patients with antibiotic infusion started within 0 to 60 minutes before incision had a lower SSI rate compared to those with infusion started within 60 to 120 minutes before incision (p = 0.04). Multivariate analysis confirmed that earlier infusion time was related to a lower risk of SSIs (OR = 0.48, 95% CI [0.25, 0.92], p = 0.027). Conclusion: Early pre-incision antibiotic administration, particularly within 0 to 60 minutes before incision, significantly reduces the risk of SSIs among surgical patients. These findings emphasize the importance of adherence to timing guidelines for preoperative antibiotic prophylaxis to improve patient outcomes and reduce healthcare-associated infections. Recommendations: Healthcare providers should prioritize the timely administration of preoperative antibiotics, aiming to initiate infusion within the hour preceding incision, to minimize the risk of SSIs in surgical patients.